DETERMINANTS OF AUDIT FEE AT PUBLIC ACCOUNTING FIRMS IN EAST JAVA - Nurkholis, Nurkholis; Krisnawan, Gede (Jurnal Aplikasi Manajemen, 2019)
This study examines the determinants of audit fee at Public Accounting Firms (KAP) in East Java, Indonesia. The determinants tested in this study consist of audit size, complexity, audit risk, non-audit services, and internal control. Respondents in this study are external auditors at KAP. Based on the convenience sampling method, the total sample in this study amounted to 60 respondents. This research uses Structural Equation Model (SEM) with SmartPLS analysis tool. The results indicate that audit size has a significant positive effect on the audit fee. Meanwhile, complexity, audit risk, non-audit services, and internal control have no significant effect on the audit fee.